Enhanced SJ Tripod Suspension Technique: Achieving Comfort and Predictable Outcomes in Severe Nasal Fracture Treatment - Joshi, Sujai; Mirza, Sidrah; Yadav, Rajesh; Ranganathan, Anbuchezian (Facial Plastic Surgery, 2025)
Managing comminuted and complicated nasal fractures is challenging because it requires obtaining both functional and cosmetic satisfaction.This research examines patient satisfaction with the closed reduction strategy paired with the use of SJ tripod suspension and splintage technique for severe nasal fractures. Our hypothesis is that proper duration of internal and external splintage is the key to satisfying results.Case series.A total of 186 consenting individuals presenting over 10 years with severe nasal fractures underwent this technique. The average duration of splintage was 10 days. Patients assessed their satisfaction using a visual analog scale.Out of the total 186 cases, 183 cases were highly satisfied with both functional (98.91%) and cosmetic (91.39%) outcomes.The tripod suspension and splintage approach is an effective and comfortable technique for the closed reduction and splintage of comminuted and complicated nasal fractures.
Keywords: closed reduction; long term splintage; tripod suspension; severe nasal fractures